Tracking the push towards extinction: combining dispersal and management data to monitor Asian longhorned beetle eradication in the U.S. - Trotter, Robert Talbot; Ryan, Josie K.; Chandler, Jennifer L.; Pfister, Scott (Frontiers in Insect Science, 2023)
In 2014, the Global Invasive Species Database identified the Asian longhorned beetle (Anoplophora glabripennis Motschulsky) as one of the 100 worst invasive species, and it has remained on that list for almost a decade. Based on the threat posed by the species many countries including the United States have adopted policies of eradication when infestations are detected. Eradicating the beetle depends on the use of visual surveys to find and destroy the individual infested trees on the landscape to both reduce the risk of spread and to push populations towards local extinction. Infestations on landscapes that span hundreds of square kilometers and require multiple surveys of millions of individual trees result in eradication efforts that can last decades. Due to the scale and duration of these efforts, tracking the progress of eradication and the impact of management activities has been a challenge. Here, we describe analyses that leverage previous reconstructions of localized beetle dispersal and large-scale data collected by eradication programs in the U.S. to quantify infestation risk at a landscape scale. The approach demonstrates a method to quantify changes in infestation risk at a hectare-scale through time to monitor eradication progress and to potentially project the impact of future management actions on the distribution and intensity of risk. We demonstrate the application of this tool using three infestations in the United States with substantial differences in beetle dispersal behavior and eradication program history.